Endoscopic treatment of Zenker's diverticulum with the stag beetle knife (sb knife) – feasibility and follow-up. (2nd October 2016) - Goelder, S. K.; Brueckner, J.; Messmann, H.
Abstract: Background and aims: Flexible endoscopic treatment of symptomatic Zenker's diverticulum (ZD) is an established treatment option. This study reports the first large cohort of ZD patients treated with the stag beetle knife (sb knife, a new scissor-like device) regarding feasibility, safety, and sustainability of mucomyotomy using this technique. Methods: From August 2013 to January 2016, n = 52 patients (pts) were treated at Klinikum Augsburg, a tertiary referral center, with the sb knife junior or standard. For stability and safety, the septum is fixed with a soft overtube before intervention. Symptoms were analyzed before and at 1 and 6 months past intervention using an extensive questionnaire of dysphagia, odynophagia, regurgitation, chronic cough, state of health, and complications. Results: The mean size of ZD was 3 cm (1–5 cm). Forty-seven out of 52 (90.4%) patients received one treatment session. The mean procedure time was 32 min (18–60 min). In 10 procedures (17%), a clip was placed at the bottom of the resection line. No major complications (e.g., perforation, mediastinitis) occurred. Five patients (9.6%) required a second treatment after a mean of 7 months (3–13) due to symptomatic recurrence. One patient was lost to further follow-up after one month with no or rare complaints. One patient had a third treatment (1.9%) without complications. During a mean follow-up of 16 months (2–31), the dysphagia score improved from 2 (1–4) prior of treatment to 1 (0–4), odynophagia, regurgitation, and chronic cough were no longer reported in the asymptomatic patients at all. Conclusions: Flexible endoscopic treatment of ZD with the sb knife and overtube is effective, safe, and has lasting effects with a relatively low recurrence rate.